2018
DOI: 10.1002/cbin.10943
|View full text |Cite
|
Sign up to set email alerts
|

Xenotopic expression of alternative electron transport enzymes in animal mitochondria and their impact in health and disease

Abstract: The mitochondrial respiratory chain in vertebrates and arthropods is different from that of most other eukaryotes because they lack alternative enzymes that provide electron transfer pathways additional to the oxidative phosphorylation (OXPHOS) system. However, the use of diverse experimental models, such as human cells in culture, Drosophila melanogaster and the mouse, has demonstrated that the transgenic expression of these alternative enzymes can impact positively many phenotypes associated with human mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It has been shown that the xenotopic expression of C . intestinalis AOX in mammalian and insect mitochondria is efficient in rescuing diverse models of mitochondrial dysfunction, especially those with OXPHOS complex IV deficiencies 30 , 31 . AOX appears to be safely expressed and to function only when the cytochrome segment of the RC is deficient 11 , 12 , which makes it an attractive enzyme to be used in future therapies for mitochondrial diseases 10 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the xenotopic expression of C . intestinalis AOX in mammalian and insect mitochondria is efficient in rescuing diverse models of mitochondrial dysfunction, especially those with OXPHOS complex IV deficiencies 30 , 31 . AOX appears to be safely expressed and to function only when the cytochrome segment of the RC is deficient 11 , 12 , which makes it an attractive enzyme to be used in future therapies for mitochondrial diseases 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The yeast Saccharomyces cerevisiae NADH reductase (Ndi1), which transfers electrons from NADH to coenzyme Q ( CoQ ), has been used to bypass CI defects 157. In a similar approach, the alternative oxidase (AOX), which transfers electrons from CoQ to molecular oxygen in different organisms, has been used to bypass CIII and IV defects in cell culture 158 and to ameliorate to different extent respiratory defects in fly models 159160. The enzyme has been successfully expressed in murine models 161, however correction of respiratory chain defects has not been shown yet in vivo in mammals.…”
Section: New Strategies To Fight Mitochondrial Derived Stressmentioning
confidence: 99%
“…Mass spectrometry revealed a complex array of metabolites in a fraction of molasses that is rich in intermediates of the TCA cycle, among other molecules, but no compound that has been tested to date could individually rescue the lethality of AOXexpressing flies cultured on LN. This suggests that AOX may cause complex metabolic changes, which could explain why the transgene is unable to rescue deleterious phenotypes of some wellestablished mitochondrial mutants (23)(24)(25)(26), and yet it was effective against genetic defects with no apparent direct link to mitochondria (27).…”
Section: Introductionmentioning
confidence: 99%